EFFECT OF PROFITABILITY, CAPITAL STRUCTURE, SHARE PRICES AND CASH FLOWS IN PREDICTING FINANCIAL DISTRESS CONDITIONS ON MANUFACTURING COMPANIES - Deasy Arisandy Aruan; Jessica Fredlina; Maggie Lifanny; Wisely Theodora (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
The purpose of this study is to see the effect of profitability, capital structure, stock prices and cash flow in predicting the condition of financial difficulties in Manufacturing companies listed on the IDX in 2018-2020 both partially and simultaneously. Financial distress is a process in which companies experience financial difficulties, financial difficulties have a very close relationship with the risk of bankruptcy that occurs in the company so that the company is unable to fulfill its obligations. The company will experience financial difficulties if the company's operating cash flow is not able to meet short-term obligations such as payment of interest on loans that have matured. The greater the obligations of the company, the greater the risk of financial difficulties. The population in this study has all manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period, which are 177 companies and the sample is 204 units of analysis. The research method applies multiple linear regression analysis techniques. The results of the study are that profitability and capital structure partially affect financial difficulties in manufacturing companies listed on the IDX in 2018-2020. Stock prices and cash flows partially have no effect on financial difficulties in manufacturing companies listed on the IDX in 2018-2020. Profitability, capital structure, stock prices and cash flow together affect the financial difficulties of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020